The role of credit rating agencies in addressing gaps in micro and small enterprise financing: The case of India - Savita Shankar (Asian Development Bank Institute (ADBI), 2019)
This paper describes the common financing challenges faced by micro, small, and medium-sized enterprises (MSMEs) in India and some important measures taken to address them, with a focus on the credit rating scheme implemented in 2000. It examines the usefulness as well as the limitations of the scheme, drawing on interviews with rating agencies and MSMEs. The analysis indicates that with credit rating being an expensive exercise, the availability of government subsidies under the scheme has been an important factor in encouraging MSMEs to get themselves rated, thereby reducing information asymmetry with banks and enabling access to credit. Given the large number of unbanked MSMEs in the country, leveraging the data generated by MSME lending and credit rating in the country through the creation of a credit risk database is necessary. Lenders will then be able to tap into the collective data generated in order to make more informed credit decisions with regard to MSMEs without relying on subsidies.
Keywords: G21; G28; G38; 330; micro; small; and medium-sized enterprises; India; credit rating